2016
DOI: 10.30539/iraqijvm.v40i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological study of the kidneys and salt glands in great flamingos (Phoenicopterus roseus)

Abstract:      This study was designed to explain the anatomy and histology of kidneys and salt glands in Great Flamingos. Eight adult healthy Great Flamingos of both sexes have been used. The results showed that the kidneys in Great Flamingos consist of three separated lobes. The right kidney was longer 8.9±0.3 mm than the left kidney 8.4±0.4mm. The ratio of the kidneys weight to the total body weight was 0.39%. The salt gland was very large crescent shape, and occupied the supraorbital fossa and has 20.8±0.2mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…The secretary tubules are lining with a single layer of principal cuboidal cells forming a narrow lumen , the peripheral blind end of the tubules are lined round peripheral cells. This histological observed of the salt glands are in agreement with the results of many workers whom studied the histological structures of salt gland in many water birds species such as Hussein et al (2006), Jarrar (2009), Mohammad (2012), Reshag et al (2016) and Waleed (2016). They showed that the salt gland in different avian species is consists of several longitudinal lobules composed of secretary tubules radiating from central canals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The secretary tubules are lining with a single layer of principal cuboidal cells forming a narrow lumen , the peripheral blind end of the tubules are lined round peripheral cells. This histological observed of the salt glands are in agreement with the results of many workers whom studied the histological structures of salt gland in many water birds species such as Hussein et al (2006), Jarrar (2009), Mohammad (2012), Reshag et al (2016) and Waleed (2016). They showed that the salt gland in different avian species is consists of several longitudinal lobules composed of secretary tubules radiating from central canals.…”
Section: Discussionsupporting
confidence: 91%
“…The gross or anatomical feature of the salt gland in both experiment group birds, which includes the crescent shape and supraorbital location were as the same as what was mention in all most all water birds such as (ducks, geese, common coot, moor hen, and flamingo) which was studied by (Maysoon, 2012;Hussein et al, 2006;Al-Mansour, 2014;Reshag et al, 2016). with some exception, the shape of salt gland in Kentish plovers and love birds was tubular in shape as mentioned by (Jarrar, 2009;Waleed, 2016).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The renal portal system in avian, which is different from mammals, allows the excretion of uric acid by tubular secretion (10,13,17). The vessels in this system may differ between species (5,8,12).…”
Section: Discussionmentioning
confidence: 99%